BrAPI v2: Real-world applications for data integration and collaboration in the breeding and genetics community - Selby, Peter; Abbeloos, Rafael; Adam-Blondon, Anne-Francoise; Agosto-Pérez, Francisco J.; Alaux, Michael; Alic, Isabelle; Al-Shamaa, Khaled; Aparicio, Johan Steven; Backlund, Jan Erik; Batac, Aldrin; Beier, Sebastian; Besombes, Gabriel; et al. (Oxford University Press, 2025)
Population growth and the impacts of climate change are placing increasing pressure on global agriculture and breeding programmes. Recent advancements in phenotyping techniques, genotyping technologies, and predictive modelling are accelerating genetic gains in breeding programmes, helping researchers and breeders develop improved crops more efficiently. However, these advancements have also led to an overwhelming torrent of fragmented data, creating significant challenges in data integration and management. To address this issue, the Breeding Application Programming Interface (BrAPI) project was established as a standardized data model for breeding data. BrAPI is an international, community-driven effort that facilitates interoperability among databases and tools, improving the sharing and interpretation of breeding-related data. This open-source standard is software-agnostic and can be used by anyone interested in breeding, phenotyping, germplasm, genotyping, and agronomy data management. This manuscript provides an overview of the BrAPI project, highlighting the significant progress made in the development of the data standard and the expansion of its community. It also presents a showcase of the wide variety of BrAPI-compatible tools that have been built to enhance breeding and research activities, demonstrating how the project is advancing agricultural innovation and data management practices.